Analisis Integrasi Angkutan Kota sebagai Feeder Angkutan Bus Trans Mamminasata - Muhammad Ridha Kasim; Andi Muhammad Akram; Rezki Ramadhan; Ahmad Fauzan (Syntax Literate, 2023)
Public transportation in Makassar City is not yet well integrated, be it physical integration (routes and modal shift facilities), schedule integration, and service integration (tariffs). The existence of a new mode, namely Sahabat Bus, is considered not to improve the condition of public transportation in Makassar City, but instead takes over the function of the existing city transportation. The purpose of this research is the first to find out the characteristics of the bus friend's passenger journey and the second is to find out the type of integration that can be done by bus friends and city transportation. The method used is the analysis of boarding and alighting points of passengers overlaid with bus route maps and city transportation to produce alternative stops and new stops at nodes and road sections. The results of the study show that 2. The form of physical integration that can be carried out is in the form of adding stops or points for boarding and alighting passengers at 37 alternative node points or on 15 alternative road sections based on the points and segments traversed by both modes of city transportation and Friend Bus. While the non-physical form can be carried out by collaboration between each manager or by creating a new institution specifically to operate public transportation